Macroscopic charcoal counts and areas from fours sites in the Western Ghats (India) over the past 1000 years - Nogué, Sandra; Tovar, Carolina; Bhagwat, Shonil A; Finsinger, Walter; Willis, Katherine J (PANGAEA, 2021)
High-resolution, continuously sampled charcoal records from sedimentary archives are rare in India. These datasets from four forest hollows' sedimentary sequences in an ancient agroforestry system in the Western Ghats, India, comprise the following data: (I) Macroscopic charcoal record (> 150 µm), including the total amount of particles per sample as well as the total area (mm2) of the particles per sample, and (II) Radiometric age dating (radiocarbon and Lead-210) used for depth-age modelling. More detailed information about the charcoal record and the relationships between biomass burning, vegetation change and land-use changes in the context of tropical agroforestry landscapes and sacred groves can be found in the research papers.
Keywords: agroforestry; charcoal; fire history; India; tropical forest; Western Ghats